DEVELOPMENT AND EVALUATION OF CLOBETASOL–LOADED SOLID LIPID NANOPARTICLES FOR TOPICAL TREATMENT OF PSORIASIS - REDDY, K. RAMESH; SATYANARAYANA, S. V.; REDDY, V. JAYASANKAR (International Journal of Applied Pharmaceutics, 2019)
Objective: The current research was structured to achieve a maximum topical delivery for the drug clobetasol-17-propionate (CP) and to predict the effects of various independent variables like lipid: drug ratio, surfactant, and homogenization time on particulate characters and performance solid lipid nanoparticles (SLNs). Methods: CP loaded SLNs were formulated by Emulsification–Homogenization method and optimized using 33 full factorial designs (Design-Expert software 11.0). Drug loaded SLNs were evaluated for various parameters like particle size, surface charge, polydispersity index, entrapment efficiency, surface morphology, thermal analysis, in vitro drug release through skin (Franz diffusion cell), drug deposition study and stability. Results: The optimized formulation (SLNs) attains a minimal Particle size of 133.3±3.66 nm, Poly dispersibility index of 0.179±0.081, % entrapment efficiency of 78.1±1.11 and Zeta potential of-36.2±0.11mV. Skin permeation study of CP loaded SLNs suspension showed prolonged drug release up to 24h. Maximum drug deposition was obtained after developing the drug into SLNs (48.22µg/ml) when compared to the pure drug (19.12µg/ml). Conclusion: SLNs were promising colloidal particulate carriers by which prolonged drug release and improved skin permeation was achieved for the drug Clobetasol 17- propionate.